Preliminary Study on Fish Larvae at Selected Coastal Waters of Sarawak - Muhamad, Norhakimi; Ab Rahim, Siti Akmar Khadijah (Borneo Journal of Resource Science and Technology, 2016)
A survey were carried out from April to November 2012 at five study sites namely Teluk Pandan beach, Rambungan beach, Puteri beach, Sampadi Island and Satang Besar Island, Sarawak. This survey was carried out in order to obtain early documentation of fish larvae at selected coastal waters of Sarawak. Seine net (1 mm mesh size) which was pulled by two persons at intertidal zone; and bridle net (0.5 mm mesh size) that was towed by boat at subtidal zone (Sampadi Island only) were used to collect the samples. A total of 2,562 fish larvae which comprise 25 families were obtained from both sampling methods. A total of 16 families of fish larvae were caught by seine net from the intertidal zone. The same number of families was collected at the subtidal zone of Sampadi Island by bridle net. Ambassidae, Clupeidae, Engraulidae and Gerreidae found to be dominant families in the study sites. Clupeidae and Gerreidae shown a wide larval dispersal area because they were collected at all study sites. These findings seem to indicate that the subtidal zone of Sampadi support more species of fish larvae.